(untitled) (Journal of Ideas in Health, 2024)
The history of measles spans centuries, marked by devastating outbreaks until the identification of the measles virus in the early 20th century and the subsequent development of a vaccine in 1963. Despite vaccination efforts, measles resurged globally in 2019 after years of decline. The COVID-19 pandemic further disrupted vaccination campaigns, leading to missed doses and heightened risks of outbreaks. By November 2020, over 94 million individuals were at risk of missing vital vaccines. As of May 2024, around 63 countries faced genuine measles outbreaks, with Iraq ranking third, reporting approximately 25,429 cases. Iraq’s healthcare system, already strained by decades of crises, struggles to manage the outbreak amidst challenges such as limited access to healthcare, vaccine hesitancy, and the suspension of vaccination campaigns. Urgent interventions are needed to address these challenges and prevent further escalation of the measles outbreak in Iraq.